Measurement of Dielectric Properties of Low-Density Polyethylene Nanocomposites Using “Sub-Hertz” Dielectric Spectroscopy - Mohammad Syamim Mohammad Basri; Lailatul Akmal Abdul Rauf; Mohd Hafizi Ahmad; Noor Azlinda Ahmad; Yanuar Z. Arief; Zulkarnain Ahmad Noorden (Universitas Ahmad Dahlan, 2017)
Recently, many studies have been conducted on the dielectric properties of Low-Density Polyethylene (LDPE) nanocomposites and produced different results. However, the composition of LDPE polymer and boron nitride (BN) as nanofiller has neither been well understood nor producing a convenient result. Similarly, the dielectric spectroscopy measured at “sub–hertz” frequency has been of little interest among researchers since it is often influenced by “conduction-like” effect. This research identified the dielectric properties of LDPE nanocomposites filled with hexagonal boron nitride (h-BN) nanofillers by using dielectric spectroscopy technique. The dielectric loss and relative permittivity for three different filler concentrations were investigated under “sub-hertz” frequency ranges at room temperature. The cylindrical electrode with guard ring configuration was used to conduct the experiment, in accordance to the ASTM D150 standard. The results revealed that 5 wt% filled polymer has lower loss tangent and permittivity compared to the unfilled polymer, due to the strong interaction between nano-particle and the polymer. This strong interaction is believed to limit the movement of the polymer chain. The decrease in loss tangent also indicates lower quasi-DC at low frequency. However, further increase in the filler loading has recorded an increment in the value of permittivity and loss tangent. This higher effective permittivity is mainly due to the influence of the filler permittivity.